Inovasi MSDM Untuk Branding Dan Pemasaran Digital UMKM Di Desa Cipasung Kecamatan Lemahsugih Kabupaten Majalengka - Endang Syarif; Erna Rusmiwati Sukandar (CV. SINAR HOWUHOWU, 2025)
This community service article discusses a seminar activity entitled “The Human Resource Management Innovation in Supporting Branding and Digital Marketing of UMKM Products” conducted in Cipasung Village, Lemahsugih District, on August 29, 2025. The purpose of this activity was, to enhance the capacity of Micro, Small, and Medium Enterprises (UMKM) actors and PKK cadres in facing the digital era, particularly in branding, digital marketing, and human resource management aspects. The method used was a participatory seminar consisting of material presentation, interactive discussion, case studies of successful UMKM, and simple mentoring by students. The results showed to increase participant awareness of the importance of digital marketing and branding as business identity. Several UMKM actors began to consider creating logos, improving product packaging, and utilizing social media and digital platforms for promotion and sales. This activity demonstrates that educational seminars and direct mentoring can effectively encourage UMKM’ readiness for digital transformation at the village level.